Multi-sensor time synchronization algorithm based on Gaussian process regression - Yang, Quan; Zhao, XuanZhi; Zhang, Wen; Jin, WenJun (Journal of physics. Conference series, 2022)
In order to address the problem of inconsistent sampling frequency and accuracy of each sensor in multi-sensor data fusion technology, the algorithm of Gaussian Process Regression (GPR) is proposed for time alignment, and in the scenario where the target motion model is uniform linear motion and uniform turning motion, the simulation is compared and analyzed respectively. The simulation results show that the proposed algorithm can effectively improve the accuracy of time synchronization.